Temporomandibular joint condylar changes following maxillomandibular advancement and articular disc repositioning - Gonçalves, João Roberto [UNESP]; Wolford, Larry Miller; Cassano, Daniel Serra [UNESP]; Da Porciuncula, Guilherme [UNESP]; Paniagua, Beatriz; Cevidanes, Lucia Helena (Elsevier, 2013)
Purpose To evaluate condylar changes 1 year after bimaxillary surgical advancement with or without articular disc repositioning using longitudinal quantitative measurements in 3-dimensional (3D) temporomandibular joint (TMJ) models. Methods Twenty-seven patients treated with maxillomandibular advancement (MMA) underwent cone-beam computed tomography before surgery, immediately after surgery, and at 1-year follow-up. All patients underwent magnetic resonance imaging before surgery to assess disc displacements. Ten patients without disc displacement received MMA only. Seventeen patients with articular disc displacement received MMA with simultaneous TMJ disc repositioning (MMA-Drep). Pre- and postsurgical 3D models were superimposed using a voxel-based registration on the cranial base. Results The location, direction, and magnitude of condylar changes were displayed and quantified by graphic semitransparent overlays and 3D color-coded surface distance maps. Rotational condylar displacements were similar in the 2 groups. Immediately after surgery, condylar translational displacements of at least 1.5 mm occurred in a posterior, superior, or mediolateral direction in patients treated with MMA, whereas patients treated with MMA-Drep presented more marked anterior, inferior, and mediolateral condylar displacements. One year after surgery, more than half the patients in the 2 groups presented condylar resorptive changes of at least 1.5 mm. Patients treated with MMA-Drep presented condylar bone apposition of at least 1.5 mm at the superior surface in 26.4%, the anterior surface in 23.4%, the posterior surface in 29.4%, the medial surface in 5.9%, or the lateral surface in 38.2%, whereas bone apposition was not observed in patients treated with MMA. Conclusions One year after surgery, condylar resorptive changes greater than 1.5 mm were observed in the 2 groups. Articular disc repositioning facilitated bone apposition in localized condylar regions in patients treated with MMA-Drep. © 2013 American Association of Oral and Maxillofacial Surgeons.
Keywords: adolescent; adult; aged; clinical article; cone beam computed tomography; female; follow up; human; image analysis; longitudinal study; male; mandible reconstruction; maxillomandibular advancement; nuclear magnetic resonance imaging; quantitative analysis; skull base; temporomandibular joint